2007
DOI: 10.1038/sj.bjp.0707180
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in the regulation of mRNA for M2 muscarinic acetylcholine receptors and endothelial and neuronal NO synthases in rat atria

Abstract: Background and purpose: Agonists of the M 2 muscarinic acetylcholine receptor (mAChR) increase mRNA for this receptor and mRNA for endothelial and neuronal isoforms of NO synthase (eNOS or nNOS). Here we examine the different signalling pathways involved in such events in rat cardiac atria. Experimental approach: In isolated atria, the effects of carbachol on mRNA for M 2 receptors, eNOS and nNOS were measured along with changes in phosphoinositide (PI) turnover, translocation of protein kinase C (PKC), NOS ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Moreover, treatment with low concentrations of acetylcholine in epithelium‐denuded bronchi increased NO release. Intriguingly, NO‐mediated bronchorelaxation, secondary to M 2 muscarinic receptor activation, is more marked at lower than higher acetylcholine concentrations (Sterin‐Borda et al ., 1995; Range et al ., 1997; Ganzinelli et al ., 2007). In any case, in the present study, the maximal BNP‐dependent relaxant activity also increased in iNOS transcripts, confirming that NO synthesis plays a role in the downstream mechanisms of BNP‐dependent control of bronchial tone (Hamad et al ., 1997; Range et al ., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, treatment with low concentrations of acetylcholine in epithelium‐denuded bronchi increased NO release. Intriguingly, NO‐mediated bronchorelaxation, secondary to M 2 muscarinic receptor activation, is more marked at lower than higher acetylcholine concentrations (Sterin‐Borda et al ., 1995; Range et al ., 1997; Ganzinelli et al ., 2007). In any case, in the present study, the maximal BNP‐dependent relaxant activity also increased in iNOS transcripts, confirming that NO synthesis plays a role in the downstream mechanisms of BNP‐dependent control of bronchial tone (Hamad et al ., 1997; Range et al ., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exercise increases eNOS expression in heart tissue (Grijalva et al 2008). Previous studies have indicated that nNOS and eNOS up-regulate M 2 receptor gene expression in rat hearts (Ganzinelli et al 2007), so this mechanism may contribute Fig. 6 Expression changes of M 2 receptors in the left ventricle of rats in the control (CON), aerobic training (AT), hyperlipidemia (HL), and hyperlipidemia plus aerobic training (HL + AT) groups.…”
Section: Hyperlipidemia Avects the Expression Of Cholinesterase-positmentioning
confidence: 97%
“…The activation of the vagus nerve is therefore hypothesized to be reduced in the HL animals, given that the NO-cGMP pathway facilitates ACh release (Danson and Paterson 2003). In addition, endothelial nitric oxide synthase (eNOS) is veriWed to be decreased in hyperlipidemia, which down-regulates M 2 receptors expression (Ganzinelli et al 2007).…”
Section: Hyperlipidemia Avects the Expression Of Cholinesterase-positmentioning
confidence: 99%
“…nNOS gene regulation in tissues other than the myocardium. The genomic regulation (transcriptional and translational mechanisms) of cardiac nNOS is sparse, despite increased expression of nNOS mRNA and protein in LV or in atria following various pathophysiological insults (Takimoto et al 2002;Damy et al 2004;Danson et al 2004;Ganzinelli et al 2007). Understanding the transcriptional control of nNOS is important in defining the transcription/translation of specific nNOS splice variants in cardiovascular normal physiology and diseases.…”
Section: The Nnos Gene Transcription and Regulation Nnos Gene Multimentioning
confidence: 99%
“…; Ganzinelli et al . ). Understanding the transcriptional control of nNOS is important in defining the transcription/translation of specific nNOS splice variants in cardiovascular normal physiology and diseases.…”
Section: Introductionmentioning
confidence: 97%